Cultural competence among health care professionals in a tertiary care setting. - Giri, Asmita (2021)
ABSTRACT: Background: Cultural competence is about health care professionals being able to take the patient's cultural background, beliefs, values and traditions into consideration in patient care. Growth of multicultural societies have highlighted the need to possess knowledge and skills that are necessary to care for all patients who seek help from the health care services, regardless of their cultural background. Aim: To assess cultural competence among health care providers of tertiary care setting. Material & methods: A cross-sectional analytical study was used for the study, involving 290 health care personals employed in the largest tertiary care hospital of Nepal undergoing selection through non probability sampling i.e. convenience sampling method. Data was collected using Cultural Competence Assessment (CCA), a self administered tool. The statistical software SPSS window-26 was used to entry and analyze the data. Descriptive statistics, including frequency distributions and measures of central tendency were employed to analyze demographic information (independent variables) and the cultural competence levels (dependent variables), while inferential statistics, such as independent t-test, chi-square test and one-way analysis of variance (ANOVA) were operated to compare the means. Results: Very limited number (6.2%) of professionals have acquired the cultural diversity training. The overall level of cultural competence among health care providers was moderate. Gender and current roles of health care providers were related to self perceived cultural competence and the subscales of cultural awareness/sensitivity. Significant association of self-perceived capacity existed with educational variables. Regarding the "types of training", statistical significance was established with self perception of being competent or incompetent and the culturally competent behavior. Conclusion: This study shows the sympathetic scenario of culturally competent care. Consideration of involved factor and customized designation of diversity training, specific to health care setting could be a key attempt in holistic healing process. Keywords: Culture, Competence, Health care professionals.